TOTAL PLATE COUNT IN CHICKEN BROILER MEAT SOLD IN SOME TRADITIONAL MARKETS IN SOUTH DENPASAR - Manullang, Martha Putri; Swacita, Ida Bagus Ngurah; Suada, I Ketut (Buletin Veteriner Udayana; Vol. 12 No. 1 Pebruari 2020, 2020)
This study aims were to determine the overall amount of bacterial contamination in some traditional markets of South Denpasar District using Total Plate Count test. Sampling was conducted in four traditional markets and each market was picked up by three marketers with six repetitions. The measured variable is the amount of TPC contamination on broiler chicken grown on Nutrient agar medium. The measurement data were analyzed by ANOVA test and then continued with Duncan's new Multiple Range Test. The results showed that the amount of TPC contamination in broiler meat on Nyanggelan Market 45.58x10 4 CFU/g, Sudha Merta Market 47.28x10 4 CFU/g, Kertha Boga Market 55.64x10 4 CFU/g and market of I Made Putra 5808x10 4 CFU/g and after analyzed statistically between Nyanggelan Market with Sudha Merta Market and between Market Kertha Boga with Market of Made Putra is not significantly different (P>0.05). While between Nyanggelan market and Sudha Merta Market with Kertha Boga Market and I Made Putra Market is significantly different (P<0.05). Based on the result of the research, it can be concluded that TPC contamination in broiler chicken sold in some markets in South Denpasar Subdistrict is still below standard limit so it is feasible to be consumed.